Identification of novel mutations in hemochromatosis genes by targeted next generation sequencing in Italian patients with unexplained iron overload. Issue 4 (June 2016) - Badar, Sadaf; Busti, Fabiana; Ferrarini, Alberto; Xumerle, Luciano; Bozzini, Paolo; Capelli, Paola; Pozzi‐Mucelli, Roberto; Campostrini, Natascia; De Matteis, Giovanna; Marin Vargas, Sergio; Giorgetti, Alejandro; Delledonne, Massimo; et al.
Abstract : Hereditary hemochromatosis, one of the commonest genetic disorder in Caucasians, is mainly associated to homozygosity for the C282Y mutation in the HFE gene, which is highly prevalent (allele frequency up to near 10% in Northern Europe) and easily detectable through a widely available "first level" molecular test. However, in certain geographical regions like the Mediterranean area, up to 30% of patients with a HH phenotype has a negative or non‐diagnostic ( i.e . simple heterozygosity) test, because of a known heterogeneity involving at least four other genes ( HAMP, HJV, TFR2, and SLC40A1 ). Mutations in such genes are generally rare/private, making the diagnosis of atypical HH essentially a matter of exclusion in clinical practice (from here the term of "non‐HFE" HH), unless cumbersome traditional sequencing is applied. We developed a Next Generation Sequencing (NGS)‐based test targeting the five HH genes, and applied it to patients with clinically relevant iron overload (IO) and a non‐diagnostic first level genetic test. We identified several mutations, some of which were novel ( i.e. HFE W163X, HAMP R59X, and TFR2 D555N) and allowed molecular reclassification of "non‐HFE" HH clinical diagnosis, particularly in some highly selected IO patients without concurring acquired risk factors. This NGS‐based "second level" genetic test may represent a useful tool for molecular diagnosis of HH in patients in whom HH phenotype remains unexplained after the search of common HFE mutations. Am. J. Hematol. 91:420–425, 2016. © 2016 Wiley Periodicals, Inc.